A novel chemo-enzymatic synthesis of hydrophilic phytosterol derivatives. (1st February 2016) - He, Wen-Sen; Hu, Di; Wang, Yu; Chen, Xue-Yan; Jia, Cheng-Sheng; Ma, Hai-Le; Feng, Biao
Highlights: A novel chemo-enzymatic route was developed. Hydrophilic phytosterol derivatives were successfully synthesized. The water solubility of phytosterols was greatly improved. Abstract: In this study, a novel method was developed for chemo-enzymatic synthesis of hydrophilic phytosterol derivatives, phytosteryl polyethylene glycol succinate (PPGS), through an intermediate phytosteryl hemisuccinate (PSHS), which was first chemically prepared and subsequently coupled with polyethylene glycol (PEG) through lipase-catalyzed esterification. The chemical structure of intermediate and goal product were finally confirmed to be PSHS and PPGS by FT-IR, MS and NMR, suggesting that hydrophilic phytosterol derivatives were successfully synthesized. The effects of various parameters on the conversion of PSHS to PPGS were investigated and the highest conversion (>78%) was obtained under the selected conditions: 75 mmol/L PSHS, 1:2 M ratio of PSHS to PEG, 50 g/L Novozym 435, 120 g/L 3 Å molecular sieves in tert -butanol, 55 °C, 96 h and 200 rpm. The solubility of phytosterols in water was significantly improved by coupling with PEG, facilitating the incorporation into a variety of foods containing water.